Volatile exchange rates and speculation: can the dollar movements of the 1980s be explained? - Antti Urvas (Bank of Finland, 1991)
The paper analyzes why exchange rates can deviate substantially from levels predicted by economic fundamentals. Chapter 2 reviews traditional exhange rate models and shows how they fail. Since speculation seems to·play a role in exchange rate determination, speculation and expectations formation are discussed in chapter 3. Chapters 4 and 5 review results from latest studies in exchange rate determination and short-term behaviour of the foreign exchange market. News' role and for~ ign exhange market's efficiency are discussed in chapter 6. Chapter 7 describes the speculative nature of the foreign exhange market, market's development in 1980s and central banks' role in the market.
URN:NBN:fi:bof-201808011812
Keywords: 330